The street with no name [videorecording (DVD)] - Keighley, William, 1889-1984; Stevens, Mark, 1916-1994; Widmark, Richard; Nolan, Lloyd (Fox film noir, 2005)
Determined to unravel a crime, FBI Inspector Briggs sends his best agent undercover to penetrate the inner circle of the notorious Stiles gang. Everything goes according to plan, until an informant inside the police department tips off Stiles.